Innovation, sustainability and organizational change in a social Portuguese organization: a strategic management perspective - Barbosa, Fernando de Oliveira (2018)
Social economy organizations are mission driven with the purpose of creating social value, overcoming a social problem and contributing to attain sustainable social development. In this chapter, a particular weakness underlying those organizations is addressed: lack of managerial skills and the importance of a well-structured process of strategic management and organizational innovation. Based on the analysis of a Portuguese case study, the goal is to increase the knowledge on the facilitating factors and barriers to the improvement of the quality of service and the efficiency of the management of a social economy organization, in order to understand how it creates and delivers social value and ensures its future sustainability. The findings highlight a number of best practices in the design of a structured innovation process which were supported by the Portuguese Program Q3-Qualifying the Third Sector, which may help similar organizations to improve their innovation and organizational processes.